Decoding Genetic Risk: A Genome-Wide Association and Functional Analysis of Variants Linked to Liver Cancer Susceptibility: Analysis of Variants Linked to Liver Cancer Susceptibility - danang prasetyaning amukti; Daru Estiningsih; Tetie Herlina; Latifa Amalia; Ifa Aris Suminingtyas; Moch. Saiful Bachri; Ria Indah Pratami; Imam Akbar; Muhammad Ma’ruf (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2026)
Liver cancer is one of the leading causes of cancer death worldwide. Genetic factors play a role in determining a person's susceptibility to this disease. Genome-Wide Association Studies (GWAS) have identified several genetic variants associated with liver cancer, but their functional mechanisms still need to be further explored. Therefore, this study aims to identify genetic variants that contribute to liver cancer, evaluate their functional effects on proteins, analyze allele frequencies across global populations, and examine gene expression in various human tissues. This study used a bioinformatics approach to identify genetic variations associated with liver cancer from the GWAS Catalog. Five selected missense variants were analyzed using SIFT and PolyPhen-2 to assess their functional impact. Allele distributions in the global population were analyzed using 1000 Genomes Project data, and gene expression was analyzed using the GTEx Portal. The analysis identified 77 candidate genes with significant associations with liver cancer, based on p-values meeting the threshold (p < 5 × 10⁻⁸). Five genes in the Missense Variant category showed a strong association with liver cancer: IFNL3, SLC30A10, PNPLA3, OSMR, and CMTR2. In the analysis using SIFT and PolyPhen-2, the rs3096380 variant (CMTR2) was deleterious, and rs738409 (PNPLA3) and rs188273166 (SLC30A10) were deleterious and probably damaging, with the potential to disrupt protein function and contribute to the pathogenesis of liver cancer. Conclusion: Genetic variations rs738409 (PNPLA3) and rs188273166 (SLC30A10) are deleterious and probably damaging, potentially disrupting protein function and contributing to liver cancer pathogenesis.